2019
DOI: 10.3889/oamjms.2019.852
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Low-Dose Naloxone to Intrathecal Morphine on Postoperative Pain and Morphine Related Side Effects after Cesarean Section: A Double-Blind, Randomized, Clinical Trial

Abstract: BACKGROUND: Nowadays, spinal anaesthesia is a suitable choice for most elective and emergency cesarean section (C-section) deliveries. AIM: This study aimed to determine the effect of adding low-dose naloxone to intrathecal morphine on postoperative pain and morphine related side effects after C-section. MATERIAL AND METHODS: In the present double-blind, randomised clinical trial, 70 women aged over 18 years, who were candidates for elective medical C-section under spinal anaesthesia were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The use of long-acting opioid analgesic techniques like intrathecal morphine or modified-release oral opioids not only prolongs the duration of analgesia but also can extend the duration of PONV 70 72 . In one study, naloxone was added to intrathecal morphine and significantly decreased the severity of postoperative nausea and pruritus after cesarean section 73 .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…The use of long-acting opioid analgesic techniques like intrathecal morphine or modified-release oral opioids not only prolongs the duration of analgesia but also can extend the duration of PONV 70 72 . In one study, naloxone was added to intrathecal morphine and significantly decreased the severity of postoperative nausea and pruritus after cesarean section 73 .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Cuando la morfina se administra correctamente, ajustando las dosis a las características del paciente, la depresión respiratoria es limitada y rápidamente se desarrolla tolerancia a este efecto. Deben tomarse precauciones adicionales si la morfina se administra a pacientes con enfermedades obstructivas respiratorias, enfermedades cardiovasculares o en pacientes que se encuentren bajo tratamiento con fármacos que deprimen el sistema nervioso central (3) . En el caso de la ketamina, este fármaco no produce efectos depresivos directos sobre el sistema respiratorio salvo que sea administrado de forma rápida y a dosis altas (7,8) .…”
Section: Discussionunclassified
“…La morfina resulta ser el analgésico opiáceo por excelencia y el punto de referencia para los demás opioides. A pesar de la síntesis de nuevos opioides, sigue siendo la piedra angular en el tratamiento del dolor moderado-severo y dentro de éste, el dolor postoperatorio por su disponibilidad en una gama amplia de presentaciones, por su farmacocinética y farmacodinamia bien definidas y su relativo bajo costo (3) .…”
unclassified
“…The studies have shown that intrathecal opioids and low-dose intrathecal naloxone can successfully treat nausea and pruritus while also perhaps providing excellent postoperative pain management (9,29) .…”
Section: Discussionmentioning
confidence: 99%